Detection of lung allograft injury through a comprehensive multidisciplinary analysis of donor-derived cell-free DNA in plasma and bronchoalveolar lavage: a real-world single center experience - Calabrese, Fiorella; Pezzuto, Federica; Vedovelli, Luca; De Chellis, Cecilia; Lunardi, Francesca; Loy, Monica; Faccioli, Eleonora; Vadori, Marta; Biondini, Davide; Marinello, Serena; Braccioni, Fausto; Meloni, Federica; et al. (Frontiers in Immunology, 2025)
IntroductionPlasma donor-derived cell-free DNA (dd-cfDNA) is an emerging potential tool for diagnosing lung graft injury. This study explored the relevance of dd-cfDNA levels in different graft injuries thoroughly characterized after a well-established multidisciplinary team approach. The usefulness of bronchoalveolar lavage (BAL) dd-cfDNA in complementing detection of allograft injury was also investigated.MethodsPlasma dd-cfDNA was measured by next generation sequence on 127 samples from patients visited consecutively, contemporaneously with a systematic analysis of surveillance transbronchial biopsy by LASHA template, BAL analysis and immunological monitoring.ResultsPatients with immunological injury exhibited the highest plasma dd-cfDNA levels (median 2.67%), with a sensitivity of 100% while patients with non-immunological insults showed a sensitivity of 28%. The combination of BAL with plasma dd-cfDNA improved the sensitivity for detecting non-immunological injury from 28% to 71%. Random forest analysis showed that plasma dd-cfDNA >1% was among the most important variables in predicting death and chronic lung allograft dysfunction.DiscussionOur data suggests that plasma dd-cfDNA is a useful tool for immunological graft injury assessment. The performance of BAL dd-cf DNA needs to be validated on larger case series. The integration of plasma dd-cfDNA with other post-transplant follow-up investigations may allow more sensitive diagnoses and appropriate graft injury management.